(untitled) (Memoria y Civilización, 2009)
In Western Europe before the Great War aeroplanes and airships were charged with national symbolism because they displayed the technical superiority of particular nations. In addition the nations were represented as performative acts within big events like air shows and cross-country flights when crowds of people lined the flight route. This was especially the case when the German airship Zeppelin travelled along the Rhine bringing the nation together as it was viewed as an "imagined community" (Benedict Anderson). In France the big aviation meetings led to the unification of a nation that had been divided after the Dreyfus Affair. The aeroplane was regarded as a symbol of progress. In the United Kingdom in contrast the development in aeronautics was taken more sceptically. One again the Royal Navy asserted its position as a national symbol.